The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1136/bmjopen-2018-021629
|View full text |Cite
|
Sign up to set email alerts
|

Episiotomy practice in six Palestinian hospitals: a population-based cohort study among singleton vaginal births

Abstract: ObjectiveTo explore the rates, characteristics and indications for episiotomy among women delivering vaginally for the first time, as well as parous women.Study designA prospective, population-based birth cohort study.SettingObstetric departments in six Palestinian government hospitals.ParticipantsAll women with singleton vaginal births (n=29 165) from 1 March 2015 until 1 March 2016.MethodsAll women were divided into two groups: first vaginal birth group (n=9108), including primiparous women and women with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 16 publications
0
15
1
4
Order By: Relevance
“…The combination of such characteristics is of major importance to accurately analyze practices because the episiotomy rates varied broadly: multiparous women at term with cephalic presentation and without instrumental delivery (Group 3) had the lowest rate of episiotomy, while nulliparous women at term with cephalic presentation and with instrumental delivery (Group 2) had the highest rate. Even if the other groups [57], and accounted for only 6% of all episiotomies, our results highlight a significant rate in instances of prematurity, breech birth and multiple pregnancy, which are frequently omitted from randomized trials or cohort studies [7, 14, 18, 22, 39, 40].…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The combination of such characteristics is of major importance to accurately analyze practices because the episiotomy rates varied broadly: multiparous women at term with cephalic presentation and without instrumental delivery (Group 3) had the lowest rate of episiotomy, while nulliparous women at term with cephalic presentation and with instrumental delivery (Group 2) had the highest rate. Even if the other groups [57], and accounted for only 6% of all episiotomies, our results highlight a significant rate in instances of prematurity, breech birth and multiple pregnancy, which are frequently omitted from randomized trials or cohort studies [7, 14, 18, 22, 39, 40].…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies [14, 1922] have limited their analyses to overall episiotomy rates or in case of instrumental delivery [37, 38], but no classification has been used so far. The first 4 groups of our classification combine four parameters: parity, term, presentation and mode of delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Another study also suggested that episiotomy is used only if there was an indistinct indication of imminent tearing. 7 There is wide variation in the rates of episiotomy all over the world, from developed countries such as Denmark (4%), 10 Sweden (9.7%), the UK (12%-15%) and the USA (11.6%) 11 12 to developing countries including Saudi Arabia (45%), 13 India (60%), 14 Jordan (67%), Yemen (75.1%), 15 Cambodia (94.5%) 16 and China Taiwan (100%), 12 which are still very high compared with the 10% recommended by the WHO. 6 However, in 2010, the prevalence of third-degree or fourth-degree tears was not significantly different in Denmark (4.1%), Sweden (3.5%), the UK (2.4%-3.2%), the USA (4.9%), India (2.1%) and China (4.9%).…”
Section: Open Accessmentioning
confidence: 99%
“…In 2005, Wick et al [ 19 ] published a study comparing routine practices of normal childbirth in eight Palestinian maternity units with the evidence-based guidelines and reported that six of eight units used routine episiotomy for primiparous women. Indeed, a more recent study by Zimmo et al [ 20 ], including six governmental maternity units in Palestine, has shown an overall episiotomy rate of 28.7% and 78.8% among women having their first vaginal birth.…”
Section: Introductionmentioning
confidence: 99%